The Effect Of Workload And Work Discipline On The Performance Of Employees Of Bungursari Tasikmalaya Health Center - Surya, Tirta Haidar; Rahwana, Kusuma Agdhi; Lestari, Suci Putri (Jurnal Fokus Manajemen, 2024)
This study aims to determine the Effect of Workload and Work Discipline on the Performance of Bungursari Tasikmalaya Health Center Employees. The method used was a quantitative approach with a research sample of 33 respondents of Bungursari Tasikmalaya Health Center employees. The data used are primary and secondary data. The analysis tool used in this study is multiple linear regression analysis using SPSS version 23. The results showed that simultaneously Workload and Work Discipline had a significant effect on Employee Performance. Partially Workload has no effect on performance. Partially, Work Discipline has a significant effect on Employee Performance.